A safe harbor: Wealth-income ratios in Switzerland over the 20th century and the role of housing prices - Enea Baselgia; Isabel Martínez (ETH Zurich, KOF Swiss Economic Institute, 2020)
We estimate the ratio of private wealth to national income, Øpt, for Switzerland over the period 1900-2018. Our results indicate that the development of Øpt in Switzerland did not follow a U-shaped pattern as in most European countries, but that the evolution was extraordinarily stable, with Øpt oscillating around 500% over most of the 20th century. However, the wealth-income ratio has been on the rise since the turn of the century to reach 721% in 2017-an unprecedented level in the past. This considerable increase is mainly driven by large capital gains in housing wealth since 2010. We present new cross-country evidence that capital gains in housing wealth have become an important driver of rising wealth-income ratios in a series of developed economies.
hdl:20.500.11850/458727
Keywords: N34; D31; D33; E01; 330; wealth-income ratio; income distribution; economic growth; housing prices